PAJAK DAERAH DI 6 PROVINSI JAWA: KONTIBUSI, EFEKTIVITAS DAN DETERMINAN - Annisa Nurjannah; Marlina Ekawaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Regional economic growth is part of national economic growth. The implementation of regional development requires funds in the form of budget allocations that have been determined and obtained. Local own revenue has several sources of revenue, Provincial Tax, Regional Retribution, the results of the management of separated regional wealth and others, legitimate local original income, Provincial Tax is the largest contributor to the source of revenue Local Revenue. This research discusses the contribution, effectiveness and determinants of Provincial Taxes. This research was conducted in 6 Provinces in Jawa in 2016-2020. The data will be analyzed descriptively and regression analysis panel data. This study uses several variables, namely Inflation (X1), GDRP (X2), Total Population (X3) and Total Hotel (X4). The result of this research is inflation has a insignificant effect on local tax revenue. GDRP has a positive and significant effect on local tax revenue. Total population has a negative and insignificant effect on local tax revenue. Total hotels has a negative and significant effect on local tax revenue.